IDNLearn.com provides a comprehensive platform for finding accurate answers. Ask anything and receive immediate, well-informed answers from our dedicated community of experts.

In the following expression, the 2 distributes to the 3 and to the 4:
(2) (3+4) = (2) (3) + (2) (4)
true or false


Sagot :

Answer:

True

Step-by-step explanation:

(2) (3+4) = (2) (3) + (2) (4)

(2) (3+4)=2(7)=14

(2) (3) + (2) (4)=6+8=14

14=14 √

Thank you for participating in our discussion. We value every contribution. Keep sharing knowledge and helping others find the answers they need. Let's create a dynamic and informative learning environment together. Trust IDNLearn.com for all your queries. We appreciate your visit and hope to assist you again soon.